Use of ultrasound in differential diagnosis of soft tissue foreign bodies in children – a case series - Kawalec, Agata (Pediatria Polska - Polish Journal of Paediatrics, 2023)
There are many types of foreign bodies found in soft tissues in children. Ultrasound is a very useful tool in diagnosis. The article presents a series of cases – children with foreign bodies located in soft tissues – in which the diagnosis was confirmed with the use of ultrasound. Different features of different foreign bodies can provide information about the foreign body type (gravel, glass, wooden splinter, metal). The foreign bodies could be successfully removed under local anesthesia. Ultrasound can be used to confirm the presence of soft tissue foreign bodies in suspected patients. Moreover, the features of the image can provide information about the foreign body type. In the pediatric population, the main advantage of ultrasound is the reduction of X-rays performed.